Intertemporal decision-making as a mediator between personality traits and self-management in type 2 diabetes: a cross-sectional study - Deng, Linfang; Luo, Shaoting; Fang, Qianna; Xu, Jinjiang (Frontiers in Psychology, 2023)
Objectives: The aims to investigate the mediating effect of intertemporal decisionmaking on the association between personality traits and self-management among individuals with in Type 2 Diabetes (T2DM).Method: Patients with T2DM in the early stages of hospitalization at two tertiary hospitals in Shenyang and Jinzhou, Liaoning Province, May 2022 to January 2023.Questionnaires, including General Demographic, Self-Management, Big Five Personality, and Intertemporal Decision-Making, were administered. Pearson correlation analysis examined relationships between personality traits, intertemporal decision-making, and self-management. Hierarchical regression analysis identified self-management predictors. Mediation analysis used the PROCESS SPSS Macro version 3.3 model 4 to investigate intertemporal decision-making as mediator between personality traits and self-management.Results: Pearson correlation analysis revealed significant associations between selfmanagement scores, personality traits, and intertemporal decision-making.Hierarchical regression revealed that Neuroticism and Conscientiousness accounted for 20.8% of the variance in self-management, while intertemporal decision-making explained 4.5% of the variance. Finally, using the Bootstrap method, the mediation analysis showed that intertemporal decision-making partially mediated the effect of personality traits on self-management.Conclusion: This study emphasizes the importance of intertemporal decision-making in improving self-management behaviors among patients with T2DM. Interventions targeted at modifying intertemporal decision-making preferences could be effective in enhancing self-management behaviors, leading to better health outcomes.